EVALUASI KINERJA GURU PROFESIONAL PASCA SERTIFIKASI BENGKULU TENGAH - Sutardi, Dodo; Novrin, Edward; Sakti, Budiman (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This study aims to determine the performance of post-certification professional teachers. It was an evaluation research study using Scriven's goal-free evaluation model. The sample was selected from a population of 548 teachers receiving professional incentives in Sleman Regency, consisting of 55 teachers (5 kindergarten students, 28 elementary school students, 13 junior high school students, 7 high school students, and 7 vocational high school students), school principals, and staff of the Sleman District Education Office. Data were collected through questionnaires, interviews, FGDs, documents, and assessment sheets, and were analyzed using quantitative and qualitative descriptive techniques. The results showed that the performance of post-certification professional teachers was largely unsatisfactory, as shown by 17 indicators, 7 indicators were good and 10 other indicators were quite good.Â